Effect of nitrogen flow rate on structural, morphological and optical properties of In-rich InxAl1-xN thin films grown by plasma-assisted dual source reactive evaporation - Alizadeh, M.; Ganesh, V.; Goh, B.T.; Dee, C.F.; Mohmad, A.R.; Rahman, S.A. (Elsevier, 2016)
In-rich InxAl1-xN thin films were deposited on quartz substrate at various nitrogen flow rates by plasma-assisted dual source reactive evaporation technique. The elemental composition, surface morphology, structural and optical properties of the films were investigated by X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), Raman spectroscopy, X-ray diffraction (XRD), UV-vis spectrophotometer and photoluminescence (PL) measurements. XPS results revealed that the indium composition (x) of the InxAl1-xN films increases from 0.90 to 0.97 as the nitrogen flow rate is increased from 40 to 100 sccm, respectively. FESEM images of the surface and cross-sectional microstructure of the InxAl1-xN films showed that by increasing the N2 flow rate, the grown particles are highly agglomerated. Raman and XRD results indicated that by increasing nitrogen flow rate the In-rich InxAl1-xN films tend to turn into amorphous state. It was found that band gap energy of the films are in the range of 0.90-1.17 eV which is desirable for the application of full spectra solar cells.